Colonoscopic Findings and Histological Changes in Patients Suffering from Ankylosing Spondylitis with Normal Bowel Habit (TAJ: Journal of Teachers Association, 2010)
Ankylosing Spondylitis is a form of spondyloarthropathies characterized by chronic inflammation of the joints of axial skeleton, manifested clinically by pain and progressive stiffening of spine. It is evidenced that sero-negative spondyloarthropathies are closely related with gut inflammatory lesions. This inflammatory gut lesions may be clinically silent or with abnormal bowel symptoms. This observational study was done with an intension to see the inflammatory gut lesions in ankylosing spondylitis patients having normal bowel habit. In this study thirty eight ankylosing spondylitis patients were selected by New York revised criteria having normal bowel habit. All patients were subjected to full colonoscopy with biopsy. Only 7.89% patient showed macroscopic abnormalities (Grade-1 & 2) and 15.87 % had microscopic non-granulomatous inflammatory lesion of grade1 &2 on biopsy. This study concluded that gut inflammatory lesions in ankylosing spondylitis patients with normal bowel habit is not remarkable. So before making concrete opinion, further large sized comparable study with & without bowel symptoms can be warranted. DOI: 10.3329/taj.v22i1.5012 TAJ 2009; 22(1): 01-04